The Effect of Electronic Word of Mouth (E-WOM) and Fear of Missing Out (FOMO) on Purchase Intention toward Music Concert Tickets in Indonesia - Daniel Allen Limantara; Santi Widyaningrum; Pieter Sahertian; Aprillia Hellyani (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This study aims to examine the effect of Electronic Word of Mouth (E-WOM) and Fear of Missing Out (FOMO) on purchase intention toward music concert tickets. The study employed a quantitative approach with a causal research design. Data were collected through an online questionnaire using a five-point Likert scale. A total of 127 valid responses were analyzed after the data cleaning process. The independent variables consisted of E-WOM and FOMO, while the dependent variable was purchase intention. The data were analyzed using multiple linear regression with SPSS. The results show that E-WOM has a positive and significant effect on purchase intention, with a regression coefficient of 0.453 and a significance value of 0.000. FOMO also has a positive and significant effect on purchase intention, with a regression coefficient of 0.515 and a significance value of 0.000. Simultaneously, E-WOM and FOMO significantly influence purchase intention, as indicated by an F-value of 250.161 and a significance value of 0.000. The coefficient of determination shows that both variables explain 80.1% of the variance in purchase intention. These findings indicate that consumers’ intention to purchase music concert tickets is influenced by both informational factors from digital platforms and psychological pressure arising from social media exposure.